Um olhar para a formação de formadores em contextos on-line: os sentidos construídos no discurso coletivo - Terçariol, Adriana Aparecida de Lima (2009)
The present report is related to the Post-graduate Program in Education and Curriculum at Pontifícia Universidade Católica - São Paulo (PUC/SP), in more specifically to the follow line of research: New Technologies in Education . In this study, it was articulate the subjects of educators formation with distance education, more specifically online education , it was considered that the online mode is linked to Information and Communication Technology (TIC) and it can be considered as a way to the creation of new opportunities of formation and consequently it is a generator of new education environment oriented to Education Access. However, if we consider that to the construction of such environments it will be essential the development of initiatives that has as purpose the formation of educators, whose will act in these contexts in the role of educators. In this report we look for to identify which change indicators in the educators practice in virtual learning environment can be detached in the process of educator formation lived at Technologies and Scholar Management Project/CONSED-PUC/SP. The theory tenets that were the base to the analysis and other actions of this study draw heavily on subject that are oriented to the educator formation, online education and curriculum, whose main authors were: Philippe Perrenoud, Denise Vaillant, Fernando Albuquerque Costa and Maria Helena Peralta, Carmem Ruiz Bueno, Carlos Educardo Ferraço, Maria Elizabeth de Almeida, Rena Palloff and Keith Pratt, Ivani Fazenda, Mere Abramowicz, among others. The adopted methodology oriented to the development of this investigation is based on the qualitative research, like Case Study, once that the focus was released over a specific context that was characterized as the process of educator formation in Technologies and Scholar Projects/CONSED. As research object we considered the specialist collaborators that act in the Education Secretary in the state of Pernambuco/PE, whose we invited to develop the role as education in the course that was oriented to continuous formation and in scholar management service in this state. Herewith to start the interpretation, we began from the released register in discuss forums during the formation process, as well as we used statements that composed the reflexive memorial that was elaborated in the finish of the formation by the educators that work as object of this research. To organize the collected data it was used the software QualiQuantiSoft associated to the CDO Collective Discuss Object. Thus, the analysis put in evidence, in general way, the expectatives, impressions, advances, difficulties, strategies, emotions that showed in the developed formation. As main results, we can detached that the experience in the Project favored the educator formation to act in virtual environment, due to many factor, such: the possibility to favor the technology appropriation with the exceeding the technological language challenge, once at the final of formation, they recognized that the technology was incorporated to their lives in personal sphere as well as in their professional sphere. Another advance in the research refers to the systematization of some directives to define the role of the educator of educators from the interaction that was lived between tutor and educator during the formation activity lived in the project. The data obtained in the research can guide us to consideration related to the factor that can interfere in the implementation of continuous formation courses in online context, among ones we can detached: task accumulation, lack of technological culture, lack of strategic plan that can foreseen the re-adaptation of technological infrastructure that will be used in the formation process. Eventually, the analysis point aspects that need be considered to build a structure with methodology for the development of others project of continuous formation and in educator services that has as purpose its actuation in virtual learning environment